SEISMOTECTONICS OF THE INNER TIENSHAN: SUUSAMYR BASIN AND ADJACENT AREAS - A. V. Mikolaichuk; Z. A. Kalmetyeva; J.-P. Burg; D. Fossati; D.V. Gordeev (Геодинамика и тектонофизика)
The Ms=7.3 Suusamyr earthquake of August 19, 1992 occurred in an area reputedly aseismic. Because it was not expected there, this event attracted worldwide attention of researchers in seismology and seismotectonics, but their results have not been included in the most recent seismic zoning map of Kyrgyzstan. New studies of neotectonic structures and focal mechanisms of earthquakes in the Suusamyr area and adjacent areas give reason to revise the established notions about the seismicity of the region. The seismic hazard in Inner Tienshan appears important and Mmax are comparable to those of the Northern and Southern Tienshan, where numerous destructive events were documented in the XIX and XX centuries. For the southern parts of the study area, along Naryn River, where hydroelectric power stations are planned, the new data should be used.